Docência universitária e bacharéis docentes: processos formativos e a prática pedagógica - Rehem, Cácia Cristina França (2018)
The goal of this study was to analyze the teaching formation of bachelors and their implications in pedagogical practices, as well as the training needs requested by them. We attempted to investigate the training and pedagogical practices of bachelors/professors and discuss them in relation to the current proposals for training professors in higher education. Therefore, the theoretical framework of this work was based on the studies by paramount authors about formation: Marcelo Garcia (1999, 2009); Masetto (1998, 2012a, b); Zabalza (2014); Nóvoa (1995); Freire (1998); Imbernón (2011). As for professionalization, we followed: Imbernón (2011), Contreras (2012), Gimeno Sacristán (1995); Mas Torelló (2011), Flores (2014), Day (2001), while the pedagogic practice was based on: Masetto (1998, 2012, 2014), Mas Torelló and Tejada Fernández (2013), Zabalza (2003, 2014), Perrenoud (1993), Anastasiou (2002), Altet (2000). The research was carried out in professors that accepted voluntarily to take part in this study as long as they were bachelors. The investigation relied on qualitative approach based on case studies. The data were collected from semi-structured interviews with each professor, documents about the formation of professors in higher education (PNPGs, LDB.9.309/96, decrees 977/65 and 77/97.644 from the National Council of Education, currently Federal Council of Education, and the decree 97.644 from July 23rd 1987) and from observation of teaching classes. The data analysis revealed a scenario with few changes in the profile of these professionals in spite of the social, political, economic and cultural changes that require a new organization of teaching practices in higher education. Most of them lack specific training for teaching, while the university, the focus of this research, also lacks any initial or continuous training to professors, leading them to practice their teaching in isolation, solitude and invisibility. On the other hand, the pedagogical practice is based on a rationalistic and traditional viewpoint, based on models they have experienced as students themselves, directed by trial and error, with limited tools for teaching as a result of their non-formation. At the same time, these professors point out concerns about the practice and highlight the importance of training to help them moving towards a more qualified teaching. Thus, we consider that training is both required and possible, while we move away from a formation that is far from the university and does not advocate the pedagogical practice of the involved professors. We also witnessed the need to a formation based on relationship perspectives that are able to respecting cultural and community contexts. To accomplish these aims, it is necessary to think of a predominantly articulated and interactive space for professors, in order to stimulate them to explore and question their own knowledge, skills and practices, as well as to learn from questioning and sharing their own convictions. By this way, it should be possible to establish a necessary flow of communication, based on analyses of the educational context, to understand, interpret and interfere in essential issues for the improvement of the quality of teaching and their practices